Records Management and its Steps:An Appraisal - Jas, Nikhil Kumar (Journal of Information and Knowledge, 1995)
Presents the complete but short view of records management. Stresses the need of record management. Various categories of reocrds and the materials on which the information and data are recorded are discussed. How to organise and control records from its creation or receipt to their ultimate destruction are discussed.